Physio-Morphological Features of Chilli Accessions Under Moisture Stress Conditions - Khan, MAI; Hoque, MA; Farooque, AM; Habiba, U; Rahim, MA (Bangladesh Journal of Agricultural Research, 2012)
An experiment was carried out at the Bangladesh Agricultural University, Mymensingh during October 2005 to March 2007 to study the effect of different soil water levels on the physio-morphological features of ten Chilli (Capsicum annuum L.) accessions viz. C-0277, C-0297, BM-1, C-0100, BM-2, C-0265, C- 0272, C-0275, BM-3, and C-0271. The experiment was set up in pots under glasshouse condition. The water treatments were applied at 4 vegetative growth stages following withholding method (crude method) starting from 25 days after sowing and thereafter at every 7 days interval until final stage. The water treatments applied were W1 = watering once a day; W2 = watering at 4 days interval; W3 = watering at 8 days of interval, and W0 = no watering. Moisture capacity of polybag (analogous to field capacity) was determined by subtracting leached water from the original amount of water applied. In most of the parameters studied, W2 gave the highest value, W1 and W0 gave the lowest, while W3 in between. Only a slight deviation was noticed in case of root volume and root dry weight, where W0 produced the 2nd highest and highest values, respectively. The effects of different water treatments on all the growth parameters studied was significant in case of all accessions and growth stages. The accessions C-0271, C-0277, BM-1, and C-0297 produced higher dry matter. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11229 Bangladesh J. Agril. Res. 37(2): 263-269, June 2012